Determination of the application rate and Frequency of Nimbecidine for the effective management of pea aphid Acrythosiphon pisum (Homoptera: Aphididae) on field pea - Dagne Kora; Ermias Teshome (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
The development of botanical insecticides as a novel and safer alternative strategy, botanical insecticides which contain plant extracts as active components are safer as well as environmentally friendlier than synthetic insecticides. The field experiment was conducted at Ginir district with the objectives to evaluate the Nimbecidine insecticide against field pea aphid and to determine the application rate and frequencies for the effective management of field pea aphid. The experiment was laid out in RCBD design with three (3) replication. The treatments include five rate of nimbecidine (3, 3.5, 4, 4.5 L/ha) and three frequencies (0, 1, 2 and 3). Aphid population significantly affected by the rate and frequency of nimbecidine at the rate 4.5 lt/ha the mortality reached from 27.89 to 10.67% on two times sprayed plots. The highest yield advantage of 35.61% and 33.86% over the untreated control was obtained from the plots treated at the rate of 4.5 and 4 lt/ha when sprayed two times. Therefore, Their use in pea aphid IPM at the rate of 4.5lt/ha at the frequency of two times application at flowering and pod setting stage provides good results.